Co-inoculation of Arbuscular Mycorrhizal Fungi and the Plant Growth-Promoting Rhizobacteria Improve Growth and Photosynthesis in Tobacco Under Drought Stress by Up-Regulating Antioxidant and Mineral Nutrition Metabolism - Begum, Naheeda; Wang, Ling; Ahmad, Husain; Akhtar, Kashif; Roy, Rana; Khan, Muhammad Ishfaq; Zhao, Tuanjie (Microbial ecology, 2022)
Drought stress is a major environmental concern that limits crop growth on a large scale around the world. Significant efforts are required to overcome this issue in order to improve crop production. Therefore, the exciting role of beneficial microorganisms under stress conditions needs to be deeply explored. In this study, the role of two biotic entities, i.e., Arbuscular mycorrhizal fungi (AMF, Glomus versiforme ) and plant growth-promoting rhizobacteria (PGPR, Bacillus methylotrophicus) inoculation in drought tolerance of tobacco ( Nicotiana tabacum L.), was investigated. The present results showed that drought stress considerably reduced tobacco plant’s growth and their physiological attributes. However, the plants co-inoculated with AMF and PGPR showed higher drought tolerance by bringing up significant improvement in the growth and biomass of tobacco plants. Moreover, the co-inoculation of AMF and PGPR considerably increased chlorophyll a, b, total chlorophylls, carotenoids, photosynthesis, and PSII efficiency by 96.99%, 76.90%, and 67.96% and 56.88%, 53.22%, and 33.43% under drought stress conditions, respectively. Furthermore, it was observed that drought stress enhanced lipid peroxidation and electrolyte leakage. However, the co-inoculation of AMF and PGPR reduced the electrolyte leakage and lipid peroxidation and significantly enhanced the accumulation of phenols and flavonoids by 57.85% and 71.74%. Similarly, the antioxidant enzymatic activity and the plant nutrition status were also considerably improved in co-inoculated plants under drought stress. Additionally, the AMF and PGPR inoculation also enhanced abscisic acid (ABA) and indole-3-acetic acid (IAA) concentrations by 67.71% and 54.41% in the shoots of tobacco plants. The current findings depicted that inoculation of AMF and PGPR (alone or in combination) enhanced the growth and mitigated the photosynthetic alteration with the consequent up-regulation of secondary metabolism, osmolyte accumulation, and antioxidant system.